The Influence Of Competence And Performance Of Bilik Hotel Training Program Alumni On Hotel User Satisfaction In The City Of Tegal - Asmungi Asmungi; Aletta Dewi Maria (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The purpose of this research is to determine and analyze the positive and significant influence of Competence and Performance of BiLiK Hotel Training Alumni on Hotel User Satisfaction in the city of Tegal. The population in this study consists of the leaders and management staff in each hotel in the city of Tegal, totaling 50 individuals. The sample used is a saturated sample, which means that the entire population becomes the research sample. The sampling technique in this study uses a questionnaire. The analysis includes validity, reliability, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results of this study show that competence (X1) has a positive and significant influence on hotel user satisfaction in the city of Tegal, and performance (X2) also has a positive and significant influence on hotel user satisfaction in the city of Tegal. Based on the F-test, both competence and performance have a simultaneous and significant impact on hotel user satisfaction in the city of Tegal. Based on the multiple linear regression test, it is found that of the two regression coefficient values of the independent variables (competence and performance), competence has the most significant influence on the dependent variable (satisfaction) with a coefficient of 0.713. Keywords : ; ;